The behaviour of remolded Batu Pahat soft clay with different OCR values under cyclic loading - Lim, Alvin John Meng Siang; Izzudini, Muhammad Arif Azraei (EDP Sciences, 2017)
The Batu Pahat Soft Clay, (BPSC) of Universiti Tun Hussein Onn Malaysia, (UTHM) were low in shear strength, bearing capacity, and suffer large settlements when subjected to loading. They undergo varies of dynamic cyclic loadings during their design lifetime and the response was typically more complex, requiring engineers to investigate the dynamic behaviour of soils thoroughly in the laboratory. The objectives of this research were to simulate remolded Batu Pahat Soft Clay (RBPSC) samples with different σv’, to study the dynamic shear modulus, G and damping ratio, D of (RBPSC) under cyclic loading with different f, OCRs, σv’ and σc’ and to analyses the correlation between G and D of the (RBPSC) with the OCR values under cyclic loading. As result, the 100 x 50 mm of remoulded samples are succeed simulated by using large strain consolidation apparatus of 50, 80 and 100 kPa of pre consolidation stress, contain moisture ranging within 42 to 55%. The series of remolded consolidated undrained dynamic cyclic triaxial test were ran under OCR of 1, 2, 3.85 and 4. Hence, it could be concluded that the G decreased when increasing of f and OCRs subjected to increasing axial strain while the G corresponding to each σv’ increases slightly as the σv’ becomes higher. The D shows minor increased when increasing of the f, OCRs and σv’ when subjected to increasing axial strain. Thus, input of parameter G and D can be review as technical values to key design structure on top of soil layer.